The Association Between Heat-Shock Protein Polymorphisms and Prognosis in Lung Cancer Patients Treated With Platinum-Based Chemotherapy - Zou, Ting; Liu, Jun-Yan; She, Li; Yin, Ji-Ye; Li, Xi; Li, Xiang-Ping; Zhou, Hong-Hao; Chen, Juan; Liu, Zhao-Qian (Frontiers in Pharmacology, 2020)
Objective: Lung cancer is one of the most prevalent cancers and the leading cause of cancer-related death in the world. Platinum-based chemotherapy plays an important role in lung cancer treatment, but the therapeutic effect varies from person to person. Heat shock proteins (HSPs) have been reported to be associated with the survival time of lung cancer patients, which may be a potential biomarker in lung cancer treatment. The aim of this study was to investigate the association between genetic polymorphisms and the prognosis in lung cancer patients treated with platinum-based chemotherapy. Methods: We performed genotyping in 19 single nucleotide polymorphisms (SNPs) of HSP genes and Rho family genes of 346 lung cancer patients by SequenomMassARRAY. We used Cox proportional hazard models, state and plink to analyze the associations between SNPs and the prognosis of lung cancer patients. Results: We found that the polymorphisms of HSPB1 rs2070804 and HSPA4 rs3088225 were significantly associated with lung cancer survival (p=0.015, p=0.049*, respectively). We also discovered the statistically significant differences between rs2070804 with age, gender, histology and stage, rs3088225 with gender and stage, which can affect lung cancer prognosis. Conclusion: The results of our study suggest that HSPB1 rs2070804 (G>T) and HSPA4 rs3088225 (A>G) may be useful biomarkers for predicting the prognosis of lung cancer patients treated with platinum-based chemotherapy.